2017
DOI: 10.1021/acs.jpclett.7b00960
|View full text |Cite
|
Sign up to set email alerts
|

Blue-Shifted Green Fluorescent Protein Homologues Are Brighter than Enhanced Green Fluorescent Protein under Two-Photon Excitation

Abstract: Fluorescent proteins (FPs) are indispensable markers for two-photon imaging of live tissue, especially in the brains of small model organisms. The quantity of physiologically relevant data collected, however, is limited by heat-induced damage of the tissue due to the high intensities of the excitation laser. We seek to minimize this damage by developing FPs with improved brightness. Among FPs with the same chromophore structure, the spectral properties can vary widely due to differences in the local protein en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 52 publications
4
62
0
Order By: Relevance
“…A well-behaved FRET donor would be easily excited by the 2-photon laser, be stable under a variety of 2-photon laser powers, and display a stable, mono-exponential lifetime[32]. To our knowledge, there is only one report of mNeonGreen’s performance using two-photon illumination[33]. This study demonstrated that blue shifted fluorescent proteins tend to perform better under 2-photon excitation than more yellow shifted fluorescent proteins but did not preclude mNeonGreen’s use from two-photon based studies.…”
Section: Resultsmentioning
confidence: 99%
“…A well-behaved FRET donor would be easily excited by the 2-photon laser, be stable under a variety of 2-photon laser powers, and display a stable, mono-exponential lifetime[32]. To our knowledge, there is only one report of mNeonGreen’s performance using two-photon illumination[33]. This study demonstrated that blue shifted fluorescent proteins tend to perform better under 2-photon excitation than more yellow shifted fluorescent proteins but did not preclude mNeonGreen’s use from two-photon based studies.…”
Section: Resultsmentioning
confidence: 99%
“…When the F 2 ratio is greater than the F 1 ratio, it is because the σ 2 of the anionic form increases upon Ca 2+ -binding while the ε changes little or not at all. The increase in σ 2 can be explained by its higher sensitivity to the local electric field compared to ε (25)(26)(27) . This sensitivity is due to a factor describing the change of the permanent dipole moment upon excitation that enters the expression for σ 2 , and the electric field affects this factor through polarizability.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the increase in σ 2 upon binding Ca 2+ is always paralleled by a shift of the one-photon absorption peak to a shorter wavelength. We previously developed a physical model ( (25)(26)(27) ) that predicts that both of these changes will happen in the anionic chromophore if the electric field directed from the center of the phenolate ring to the center of the imidazole ring increases. In red GECIs, the chromophore is oriented such that its phenolate oxygen points toward the opening of the barrel at the site of circular permutation where the Ca 2+ -sensing domain is fused to the FP (as observed for RCaMP (PDB ID: 3U0K (21) ), R-GECO1 (PDB ID: 4I2Y (21) ), and K-GECO1 (PDB ID: 5UKG (22) ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A well-behaved FRET donor would be easily excited by the 2-photon laser, be stable under a variety of 2-photon laser powers, and display a stable, mono-exponential lifetime [32]. To our knowledge, there is only one report of mNeon-Green's performance using two-photon illumination [33]. This study demonstrated that blue shifted fluorescent proteins tend to perform better under 2-photon excitation than more yellow shifted fluorescent proteins but did not preclude mNeonGreen's use from two-photon based studies.…”
Section: Mneongreen Is a Suitable Donor For Two-photon Flimmentioning
confidence: 99%